1999
DOI: 10.1083/jcb.147.7.1493
|View full text |Cite
|
Sign up to set email alerts
|

Adenine Nucleotide Translocase-1, a Component of the Permeability Transition Pore, Can Dominantly Induce Apoptosis

Abstract: Here, we describe the isolation of adenine nucleotide translocase-1 (ANT-1) in a screen for dominant, apoptosis-inducing genes. ANT-1 is a component of the mitochondrial permeability transition complex, a protein aggregate connecting the inner with the outer mitochondrial membrane that has recently been implicated in apoptosis. ANT-1 expression led to all features of apoptosis, such as phenotypic alterations, collapse of the mitochondrial membrane potential, cytochrome c release, caspase activation, and DNA de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
209
0
9

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 266 publications
(228 citation statements)
references
References 62 publications
10
209
0
9
Order By: Relevance
“…25 Reduction of ANT1 activity in either the mutant mice or in ANT1-mutant PEO patients has not been observed to increase apoptosis, 26 whereas ANT1 expression due to Ant1 cDNA transfection into nonmyogenic cultured cells has been reported to induce apoptosis. 27 However, our data suggest that increased apoptosis may not be a concern during the transduction of skeletal muscle with the Ant1 cDNA. This is because myoblasts, myotubes, skeletal muscle and heart all naturally express high levels of ANT1 and thus must be resistant to any proapoptotic effects that this protein might have.…”
Section: Discussionmentioning
confidence: 67%
“…25 Reduction of ANT1 activity in either the mutant mice or in ANT1-mutant PEO patients has not been observed to increase apoptosis, 26 whereas ANT1 expression due to Ant1 cDNA transfection into nonmyogenic cultured cells has been reported to induce apoptosis. 27 However, our data suggest that increased apoptosis may not be a concern during the transduction of skeletal muscle with the Ant1 cDNA. This is because myoblasts, myotubes, skeletal muscle and heart all naturally express high levels of ANT1 and thus must be resistant to any proapoptotic effects that this protein might have.…”
Section: Discussionmentioning
confidence: 67%
“…However, a substantial body of evidence indicates that cypD has anti-apoptotic activities. Importantly, we [120,121] and others [122] have recently found that enforced cypD expression can specifically repress the activation of the PT-pore. Another study in neuronal cells also observed apoptosis inhibition (but sensitisation for necrosis) by cypD overexpression [123].…”
Section: Overexpression Studies On Cypdmentioning
confidence: 59%
“…Pharmacological studies with CAT and BA suggest that induction of the pore function might be an irreversible process (C Brenner, unpublished data). Interestingly, only the first third of the protein is involved in apoptosis (Bauer et al, 1999) and more precisely, the region 105-156 of ANT2 has been suggested to be the binding domain of ANT with several proteins such as Bax and Bcl-2 (reviewed in Jacotot et al, 2006). Therefore, it is tempting to postulate that direct interaction of ligands with specific amino acids contained within the ANT sequence provokes a conformational change resulting in a switch from the translocase function to the pore function.…”
Section: A Lethal Pore Functionmentioning
confidence: 99%
“…More recently, a third major breakthrough has been made in terms of role of ANT in apoptosis. Thus, ANT is expressed as four tissue-specific isoforms, ANT1 to ANT4, and we and others postulated that each ANT isoform might have a specific role in influencing cell fate, notably in cancer cells (Bauer et al, 1999;Zamora et al, 2004a;Le Bras et al, 2006;Gallerne et al, 2010). In this review, we recapitulate our knowledge of the role that the various isoforms of ANT play in apoptosis, examine the expression and the function of the four ANT isoforms in cancer cells and discuss recent evidence to propose a novel classification of ANT isoforms and their function in cancer cell death.…”
Section: Introductionmentioning
confidence: 97%